Malpositioned Central Line in A Neonate Presenting as Superficial Abdominal Abscess - Garg, Manasi; Rajan, Nishanth; Dhua, Anjan; Krishnan, Lalitha (Journal of Neonatal Surgery, 2016)
Please see fulltext